Modeling an Interwoven Collimator for A 3D Endocavity Gamma Camera - Terry Lall; Yonggang Cui; Giuseppe S. Camarda; Anwar Hossain; Ge Yang; Utpal N. Roy; Ralph B. James (AIMS Medical Science, 2016)
Positron emission tomography (PET) and single-photon emission-computed tomography (SPECT) are important nuclear-medical imaging tools in diagnosing cancers and creating effective treatment plans. Commercially imaging systems are operated externally and can create 3D images of the whole body or of specific organs by rotating the gamma-ray detectors, and then employing software to reconstruct the 3D images from the multiple 2D projections at different angles of view. However, their uses in intraoperative environments or for imaging specific small organs, e.g., the prostate, ovary, and cervix, are limited because of their bulky designs and the long working-distance, hence causing low efficiency and poor spatial-resolution. In such situations, compact imaging devices, e.g., the trans-rectal gamma camera developed at Brookhaven National Laboratory (BNL) and Hybridyne Imaging Technologies, are preferable for detecting intra-prostatic tumors. The camera uses pixilated cadmium zinc telluride (CdZnTe) detectors with a matched parallel-hole collimator. However, their lack of 3D imaging capability limits their use in clinics, because the acquired images cannot be interpreted easily due to missing depth information. Given the constraint on space in such operations, the traditional 3D-image acquisition methods are impractical. For this reason, we designed an interwoven collimator dedicated for 3D imaging using an endocavity probe. This novel collimator allows us to take two or multiple views of a specific organ or tissue without rotating the camera. At the first stage of design for the collimator, we carried out Monte-Carlo simulations to study the response of the collimator and the attached detectors to gamma rays, and then developed a maximum-likelihood-based algorithm for reconstructing 3D images. In this paper, we detail our modeling of the collimator on a cluster Linux computer, and discuss the imaging capability of this novel collimator.